2012
DOI: 10.5007/1980-0037.2012v14n6p636
|View full text |Cite
|
Sign up to set email alerts
|

Perfil antropométrico e adiposidade abdominal de escolares entre 6 a 10 anos de idade do Sul do Brasil

Abstract: -The aims of the present study were to assess the association of anthropometric measures with body mass index (BMI) and to verify the presence of abdominal adiposity in school children. This is a cross-sectional study conducted with 4,964 school children between 6 and 10 years of age registered in 345 schools from eight municipalities of the state of Santa Catarina (Brazil). The independent variables used were the following: subscapular (SSF) and triceps skinfold (TSF) thickness, arm circumference (AC), waist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…The results found allow us to affirm that the WC provides very relevant and consistent information on the central body fat deposition in children when compared with the BMI. Corroborating the findings of this study, the studies of Soar et al 23 and Ricardo et al 24 also found a strong correlation between WC and BMI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results found allow us to affirm that the WC provides very relevant and consistent information on the central body fat deposition in children when compared with the BMI. Corroborating the findings of this study, the studies of Soar et al 23 and Ricardo et al 24 also found a strong correlation between WC and BMI.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that 33.70% of children and adolescents had a waist/height ratio over 0.5, i.e., a large fat tissue deposition in the abdominal region. This value is much greater than one found by Ricardo et al 24 , who found that 11.90% of children between 6 and 10 years old had abdominal adiposity and is also greater than the one found in the McCarthy and Ashwell 25 study, in which a 11.70% prevalence was observed. According to Pereira et al 26 , the W/H index can be considered a good indicator of abdominal adiposity, even better than the isolated measurement of waist circumference, because it takes into consideration the height of the individual and allows us to establish a single cut-off point.…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the use of the measure of AC to predict excess weight were found two studies in Brazil; 11,26 however, these studies were conducted with children from 6 to 10 years, which makes it difficult to comparability of cutoff points. A study done with adolescents from 10 to 14 years of South Africa 10 verified cutoff points for AC of 22,8cm and 23,6cm for boys and girls, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other parameters have also been used for assessment of body composition, such as the waist/ height (WHR) 8,9 and arm circumference (AC). 10,11 However, these indicators are still poorly applied to predict the excess weight in children and adolescents, because for these critical values are not well established in the literature. 7 Therefore, the present study is justified by the lack of publications about the accuracy of anthropometric indicators to predict excess weight, as well as the cutting points to be used to in this condition.…”
Section: Introductionmentioning
confidence: 99%